Capacity mechanisms and the technology mix in competitive electricity markets - Pär Holmberg; Robert A. Ritz (Research Institute of Industrial Economics (IFN), 2019)
Capacity mechanisms are increasingly used in electricity market design around the world yet their role remains hotly debated. In this paper, we introduce a new benchmark model of a capacity mechanism in a competitive electricity market with many different generation technologies. We consider two policy instruments, a wholesale price cap and a capacity payment, and show which combinations of these instruments induce socially-optimal investment by the market. Changing the price cap or capacity payment affects investment only in peak generation plant, with no equilibrium impact on baseload or mid-merit plant. We obtain a rationale for a capacity mechanism based on the internalization of a system-cost externality - even where the price cap is set at the value of lost load. In extensions, we show how increasing renewables penetration enhances the need for a capacity mechanism, and outline an optimal design of a strategic reserve with a discriminatory capacity payment.
Keywords: D41; L94; 330; Investment; Wholesale electricity market; Capacity mechanism; Capacity auction; Strategic reserve